Assessment of the Genotoxic Potential of Cizolirtine a Substance-P and Calcitonin Gene-Related Peptide Release Modulator - Fernández de Henestrosa, Antonio R.; Marín, Ana-Paz; Tortajada, Araceli; Vila, Cristina; Guzmán, Antonio (Drug Research, 2020)
The analysis of the genotoxic potential of cizolirtine, a compound being developed as a drug for analgesia and for urinary incontinence, was carried out using a battery of in vitro and in vivo assays as recommended in the guidelines for medicinal products. Negative results were obtained in an Ames test (up to 5000 µg/plate), in a Mouse Lymphoma assay (up to 2000 µg/ml) and in a single dose mouse bone marrow micronucleus assay (up to 300 mg/kg). In a human lymphocyte chromosome aberration assay, a slight statistical increase in the frequency of cells with chromosome aberrations including gaps was reported for the concentrations of 200 and 1600 μg/ml at the 24-h sampling time. This minor increase in chromosome aberrations was considered of questionable biological relevance since it was moderate, was within the laboratory historical control values, did no show a dose-dependent effect and was not observed at similar concentrations in a repeat assay. Taking into considerations the results obtained in the different in vitro and in vivo assays and a weight-of-evidence analysis, it suggests that cizolirtine would not pose a genotoxic risk when administered to humans.
Keywords: genotoxic assessment; ames test; mouse lymphoma assay; chromosome aberrations assay; mouse in vivo micronuclei